Masculinized Second-to-Fourth Digit Ratio (2D:4D Ratio) Is Associated With Lower Cortisol Response in Infant Female Rhesus Monkeys (Macaca mulatta) - Wood, Elizabeth K.; Jarman, Parker; Cash, Elysha; Baxter, Alexander; Capitanio, John P.; Higley, J. Dee (Frontiers in Behavioral Neuroscience, 2020)
Second-to-fourth digit ratio (2D:4D ratio) is considered a postnatal proxy measure for degree of prenatal androgen exposure, which is the primary factor responsible for masculinizing the brain of a developing fetus. Some studies suggest that the organizational effects of prenatal androgen exposure may extend to the hypothalamic-pituitary-adrenal (HPA) axis response to stress. This study investigates the relationship between 2D:4D ratio and HPA axis functioning using a rhesus monkey (Macaca mulatta) model. Subjects were N = 268 (180 females, 88 males) rhesus monkey infants (3-4 months of age). Plasma cortisol concentrations were assayed from two blood samples obtained during a 25-hour experimental social separation stressor at two- and seven-hours post-separation. Subjects’ 2D:4D ratio was measured later in life (Mage = 6.70 years). It was hypothesized that infant rhesus monkeys that exhibited a more masculine-like 2D:4D ratio would show lower levels of circulating cortisol after a social separation and relocation stressor. Results showed that there was a sex difference in the left-hand 2D:4D ratio. Results also showed that there was an overall sex difference in cortisol concentrations and that female, but not male, monkeys that exhibited a more masculine-like right- and left-hand 2D:4D ratio exhibited lower mean stress-induced cortisol concentrations early in life. These findings suggest that higher levels of prenatal androgens in females, as measured by 2D:4D ratio, may be related to an attenuated HPA axis stress-response, as measured by plasma cortisol levels. To the extent that these findings generalize to humans, they suggest that the organizational effects of prenatal androgen exposure extend to the infant HPA axis, modulating the HPA axis response, particularly in females.